2017
DOI: 10.3892/ol.2017.7694
|View full text |Cite
|
Sign up to set email alerts
|

Function of Axl receptor tyrosine kinase in non-small cell lung cancer (Review)

Abstract: Axl receptor tyrosine kinase (hereafter Axl) is a member of the tyrosine-protein kinase receptor Tyro3, Axl and proto-oncogene tyrosine-protein kinase Mer family of receptor tyrosine kinases, possessing multiple different functions in normal cells. Axl is overexpressed and activated in numerous different human cancer types, triggering several signaling pathways and enhancing tumor progression. The present review assesses previous studies on the function of Axl in non-small cell lung cancer (NSCLC). Axl is over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 86 publications
0
38
0
Order By: Relevance
“…NSCLC is the most common histological type of lung cancer, and 70% of the patients were diagnosed with advanced stages and operative options were lost . The efficacy of the two‐drug chemotherapy regimen containing platinum in advanced NSCLC was low, and the adverse reactions were high . Therefore, it is of great significance to explore the molecular mechanism of NSCLC metastasis and new therapeutic targets to improve the prognosis of patients with NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…NSCLC is the most common histological type of lung cancer, and 70% of the patients were diagnosed with advanced stages and operative options were lost . The efficacy of the two‐drug chemotherapy regimen containing platinum in advanced NSCLC was low, and the adverse reactions were high . Therefore, it is of great significance to explore the molecular mechanism of NSCLC metastasis and new therapeutic targets to improve the prognosis of patients with NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…1B-E ). AKT and ERK signaling are two major branches of AXL signaling ( 4 , 22 , 23 ), thus their responses to R428 were determined; it was identified that R428 treatment suppressed AKT and ERK signaling activation in a dose-dependent manner ( Fig. 1B-E ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, epidermal growth factor (EGF), which activates the EGF receptor, was discovered to subsequently transactivate AXL (17). In addition, hepatocyte growth factor (HGF) was reported to activate AXL by promoting the formation of HGF receptor MET and AXL complexes (30). However, the pathway involved in the activation of AXL in the two cell lines requires further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to resistance to EGFRi, AXL overexpression has been associated with resistance to other targeted and chemotherapeutic agents in NSCLC, as recently reviewed (37). The evidence for this association is derived primarily from preclinical studies in vitro, where AXL upregulation was found in cell lines resistant to targeted agents such as PI3K inhibitors (8) or chemotherapeutics like paclitaxel, cisplatin, carboplatin, vincristine, or etoposide (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%